Mitigating Ring‐Opening to Develop Stable TEMPO Catholytes for pH‐Neutral All‐Organic Redox Flow Batteries. (9th June 2022) - Fan, Hao; Wu, Wenda; Ravivarma, Mahalingam; Li, Hongbin; Hu, Bo; Lei, Jiafeng; Feng, Yangyang; Sun, Xiaohua; Song, Jiangxuan; Liu, Tianbiao Leo
Abstract: Redox‐active organics are highly attractive in aqueous organic redox flow batteries (AORFBs). However, the lack of capacity dense, stable organic catholytes remains a challenge to develop energy‐dense, long cycle‐life AORFBs. Herein, a stable organic catholyte, 4‐[3‐(trimethylammonium)acetylamino]‐2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl chloride (TMAAcNHTEMPO) is developed through rational molecular engineering using connective acetamido and trimethylammonium groups. Paired with bis‐(trimethylammonium) propyl viologen tetrachloride anolyte, stable AORFBs (up to 1500 cycles) with a low capacity fade rate of ca. 0.0144% h −1 are achieved. Experimental characterizations and theoretical simulations revealed that TMAAcNH‐TEMPO is largely stabilized by the reduced reactivity of the nitroxyl radical moiety that mitigates a ring‐opening side reaction. Abstract : A new TEMPO molecule is developed through rational molecular engineering as a stable, capacity density organic catholyte for total organic flow batteries.